Optimalisasi Klinik Halal Untuk Legalitas Dan Sertifikasi Halal UMK: Prosendi Desa 2024 - Adenan, Moh.; Cholifah, Umi; Wulandari, Deasy; Irmadariyani, Ririn; Subagio, Ari; Priyanto, Fajar; Prasetiyaningtiyas, Susanti (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
The Village Community Service Program (Prosendi Desa) enters its second year of implementation in 2024 in Tegal Besar Subdistrict, Kaliwates District, Jember Regency. The key issues addressed are the need for support for micro and small enterprises (MSEs) in urban areas to obtain business legality and halal certification, aimed at fostering the development of the halal industry in Indonesia. The objective of this program is to assist MSEs in obtaining a Business Identification Number (NIB) in the first year and halal certification in the second year. The method used is the Participatory Rural Appraisal (PRA) approach, involving socialization, counseling, and assistance. The implications of this program include the availability of a self-declare halal certification guidebook, comprehensive assistance for MSEs in the certification process, and the acceleration of halal certification compliance as targeted by the government. Additionally, the program increases the number of MSEs with NIBs and utilizes the Halal Clinic as an implementation of agency theory to support business development.